Function of protein kinase A in hedgehog signal transduction and Drosophila imaginal disc development. - Li, W.; Ohlmeyer, J.T.; Lane, M.E.; Kalderon, D. (Cell, 1995)
Reduced protein kinase A (PKA) activity in anterior imaginal disc cells leads to cell-autonomous induction of decapentaplegic (dpp), wingless (wg), and patched (ptc) transcription that is independent of hedgehog (hh) gene activity. The resulting nonautonomous adult wing and leg pattern duplications are largely due to induced dpp and wg expression and resemble phenotypes elicited by ectopic hh expression. Inhibition of PKA in anterior cells close to the posterior compartment can substitute for hh activity to promote growth of imaginal discs, whereas overexpression of PKA can counteract transcriptional induction of ptc by hh in these cells. PKA therefore appears to be an integral component of the mechanism by which hh regulates the expression of key patterning molecules in imaginal discs.